2009
DOI: 10.1111/j.1360-0443.2008.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of supervised injection facilities and injection risk behaviours among young drug injectors

Abstract: SIFs attract highly disadvantaged drug injectors who engage none the less in less borrowing of used syringes than non-users of these facilities. The risks of indirect sharing should be emphasized when counselling SIF attendees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 14 publications
5
41
1
Order By: Relevance
“…The prevalence of HIV infection is higher than that observed in previous studies in Spain [5,32] , although it is consistent with that observed among IDUs admitted for treatment of drug abuse or dependency in 2005 (32.7%) [33] and that observed in young injectors recruited in Madrid and Barcelona (31.7%) [34] . The differences between the studies are due in part to the different methodological approaches and the different populations recruited in each case.…”
Section: Discussioncontrasting
confidence: 50%
“…The prevalence of HIV infection is higher than that observed in previous studies in Spain [5,32] , although it is consistent with that observed among IDUs admitted for treatment of drug abuse or dependency in 2005 (32.7%) [33] and that observed in young injectors recruited in Madrid and Barcelona (31.7%) [34] . The differences between the studies are due in part to the different methodological approaches and the different populations recruited in each case.…”
Section: Discussioncontrasting
confidence: 50%
“…These behavioural changes relate to PWID needle sharing behaviour outside of the SIF. Kerr et al [13] and Bravo et al [33] found that PWID who used the Vancouver SIF also reduced their needle-sharing activities significantly outside of Insite, with an odd ratio of 0.30. This has been incorporated into a number of cost-benefit and cost-effectiveness analyses for SIFs [8,14,15,18,28].…”
Section: Introductionmentioning
confidence: 99%
“…This has been incorporated into a number of cost-benefit and cost-effectiveness analyses for SIFs [8,14,15,18,28]. Because of its widespread use for Insite, and its empirical evidence [13,33] we incorporate such behavioural change for Ottawa in the analyses below.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, during the study period neither city had a naloxone distribution program, nor were there systematic measures for overdose prevention. On the other hand, both cities had supervised injection facilities, and although there are more of these facilities in Barcelona, it seems unlikely that this would have an impact on mortality [30]. We observed no difference between the two cities in the prevalence of drug use in solitary [18].…”
Section: Discussionmentioning
confidence: 75%